The Influence and Value of Analogical Thinking during New Product Ideation - Dahl, Darren W.; Moreau, Page (Journal of Marketing Research, 2002)
Although both the academic and the trade literature have widely acknowledged the need to foster the development of more-innovative products, little empirical research has examined the cognitive processes underlying the creation of these novel product concepts. In this research, three empirical studies examine how analogical thinking influences the idea-generation stage of the new product development process. The first study uses the verbal protocols of real-world industrial designers to trace the role of analogy in the context of a new product development task, and the second and third studies use an experimental approach to assess the effectiveness of different ideation strategies and conditions. Findings from these studies indicate that the originality of the resulting product design is influenced by the extent of analogical transfer, the type of analogies used, and the presence of external primes. In addition, these studies reveal a positive relationship between the originality of the product concept and consumers' willingness to pay for it, an important measure in the concept-testing phase of product development.